Evolution of access to prenatal care in Pernambuco: maternal schooling as a marker of health inequities - Daniella Oliveira Albuquerque Lins; Maria Tatiane Alves da Silva; Lívia Teixeira de Souza Maia (Revista Brasileira de Saúde Materno Infantil)
Abstract Objectives: to analyze the evolution and inequalities in prenatal care consultations in Pernambuco, according to maternal education level. Methods: this is an ecological study of pregnant women who attended seven or more prenatal consultations and resided in Pernambuco between 2011 and 2020, stratified by maternal education level and year of birth. Data were obtained from the Live Birth Information System. Temporal trend analysis was performed using the joinpoint regression method, and patterns of inequality were assessed through absolute measures (difference, ratio), relative measures (concentration index - CIX), and Equiplot-type graphs. Results: a rising trend in access to seven or more prenatal consultations among women in Pernambuco was observed between 2011 and 2020 (+3.6; p<0.001). Among women with no formal education, prenatal coverage was 47.85%, while for those with more than 12 years of education, it reached 78.15%. The Concentration Index (CIX=0.0979; p<0.001) suggests that 9.79% of prenatal access is concentrated among women with higher education levels. Conclusions: despite the expansion of prenatal care in Pernambuco, access remains unequal among women with different levels of education, highlighting maternal education as a marker of health inequities. Strategies need to be adopted to ensure greater equity in prenatal care for more vulnerable pregnant women.